Rumi motifs in the tile inscriptions of the Eminönü Yeni Valide Mosque - (:unkn) unknown (My University, 2013)
İstanbulun en işlek iskelelerinden biri olan Eminönünde, Galata Köprüsü başında yer alan Yeni Vâlide Câmii (1074/1663), mimari özellikleri bakımından olduğu kadar çini yazıtları ve çini bezemeleri açısından da önem taşımaktadır. Câminin Teknecizâde İbrahim Efendi tarafından yazılarak İznik atölyelerinde çini levhalar üzerine aktarılan celî sülüs yazıtları, zengin ve özgün bir motif repertuarını barındırmaktadır. Yazıtlarda, harflerle birlikte yer alan motifler, bitki kaynaklı motifler, rumîler, münhanî ve bulutlardır. Kendisi de dekoratif bir öğe olan yazının, harfleri arasında kalan boşlukların küçük motifler ile ayrıca süslenmesi, yazının karakterini kuvvetlendirmek olmalıdır. Bu makalede, XVII. yüzyılda kazandığı bitkisel karakteri, caminin yazıtları içindeki çeşitli ve serbest kullanımıyla göze çarpan rumi motifi üzerinde durulurken, esasında, Yeni Valide Camiinin pek farkedilmeyen bu minik bezeme öğelerine dikkat çekilmek istenmektedir.

The Yeni Valide Mosque is situated in Eminönü, one of the busiest ports of İstanbul and at the head of the Galata Bridge. It is of great importance not only in terms of the facilities it incorporates in its structure, but also for the tile inscriptions and other decorative elements it has. The tile inscriptions written by Teknecizade İbrahim Efendi in celi sülüs form and transferred on tile at İznik ateliers contain a wide range and genuine repertoire of motifs. The motifs used together with the calligraphy are flower originated forms, rumis, curves and clouds. Among those motifs, the rumis acquired their flower originated form at the XVIIth century. The aim of decorating the empty spaces by small motifs in calligraphy although it is already a decorative element in itself, should be to emphasize the character of the writing. While the various and free use of the rumi form in its floral character gained in the XVIIth century is considered in this article, it is also worthy to attract attention to these unnoticed tiny decorative details at the Yeni Valide Mosque.
Eminönü Yeni Vâlide Câmii çini yazıtlarında Rûmî motifleri
Keywords: Tarih